KAITAN ANTARA PEMBANGUNAN DAN KOMUNIKASI KRISIS DALAM ERA NEW NORMAL - Susanna Hutapea; Irene Silviani (Lembaga Penenlitian dan Pengabdian kepada Masyarakat Universitas Darma Agung, 2020)
This study aims at finding the relationship between the development and communication of the crisis in the new normal era. This research was conducted by taking information from various sources and then a summary of these sources is put together as reading material.There are many diverse responses from netizens regarding the implementation of new normal in Indonesia today. Based on World Health Organization (WHO) guidelines, everyone inevitably has to adapt to new habits so that during the Covid-19 pandemic. New normal refers to new habits that are felt uncomfortable, but must be made comfortable for the sake of survival. Like studying online at home, working from home, and refraining from leaving the house as long as the Covid-19 outbreak has not subsided. But the definition of new normal in question does not seem to be fully understood by the people of Indonesia. The majority of people understand that new normal is a suggestion to return to activities as usual, the same as before the Covid-19 pandemic occurred. In the Covid-19 crisis, the government needs to conduct effective crisis communication by conveying transparent information related to the handling of Covid-19. Failures in communication can worsen the situation and make it difficult for governments to deal with crises. Not infrequently new problems will emerge, namely the communication crisis. So, ethics in crisis communication is an important part that should not be ignored.